2005
DOI: 10.1088/0967-3334/26/5/022
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral photoplethysmography studies of the leg arterial stenosis

Abstract: A newly developed portable multi-channel photoplethysmography (PPG) device has been used for comparative studies of 20 healthy control subjects and 45 patients with diagnosed arterial stenosis in a leg. The peripheral blood pulsations were detected simultaneously at four body sites-the same fingers and toes of both arms and legs. The PPG pulses recorded at the periphery of the stenotic leg, if compared with those of the healthy leg, were much weaker, with delayed arrival as a consequence of increased pulse wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 8 publications
0
50
0
1
Order By: Relevance
“…One technique that has this potential is the optical pulse technology, photoplethysmography (PPG), [11][12][13][14][15][16][17][18] which detects changes in the blood volume in the microvascular bed of tissue. Its waveform comprises a pulsatile ("AC") physiologic waveform attributed to cardiac synchronous changes in the blood volume with each heart beat that is superimposed on a slowly varying ("DC") baseline, with various lower-frequency components attributed to respiration, sympathetic nervous system activity, and thermoregulation.…”
mentioning
confidence: 99%
“…One technique that has this potential is the optical pulse technology, photoplethysmography (PPG), [11][12][13][14][15][16][17][18] which detects changes in the blood volume in the microvascular bed of tissue. Its waveform comprises a pulsatile ("AC") physiologic waveform attributed to cardiac synchronous changes in the blood volume with each heart beat that is superimposed on a slowly varying ("DC") baseline, with various lower-frequency components attributed to respiration, sympathetic nervous system activity, and thermoregulation.…”
mentioning
confidence: 99%
“…A study by Simonson et al [60] found significant changes in the rise time in impaired arteries. The potential of differences in PTT between the left and the right sides was further stated in recent studied [61,62]. It was also shown that frequency analysis of the PPG signal can reveal differences between healthy arteries and those with arteriosclerosis [63].…”
Section: Clinical Applicationsmentioning
confidence: 81%
“…These parameters have allowed for the assessment of the vascular effects of aging, hypertension, and atherosclerosis [6] [7] [8]. Other notable applications in which PPG peak signal detection has played a key role, are related to the measurement of baroreflex sensitivity [9], diagnosis of damage to the arteries [10], as well as diagnosis of peripheral vascular disease [11], ventricular ejection time, and arterial stiffness [12].…”
Section: Introductionmentioning
confidence: 99%